The Role of Zeolite in Alleviating Lead Toxicity in Tubifex tubifex - Yeşilbudak, Burcu (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2025)
Low-cost, environmentally friendly adsorbents and catalysts have gained importance in research due to their impact on heavy metals in recent years. This study aimed to investigate the ameliorative effect of adsorbent material properties of zeolite against the lead bioaccumulation of Tubifex tubifex (Müller 1774). The oligochaete worms were exposed to 0.1 μg/l Pb, 0.1 μg/l Pb+0.1 μg/l zeolite, and 0.1 μg/l Pb+1 μg/l zeolite mixtures for 24, 48, and 96 hours. Lead accumulation in the whole body and environmental media of T. tubifex was determined by inductively coupled plasma mass spectrometry (ICP-MS). Lead toxicity increased with increasing durations of exposure. In all groups, lead accumulation was obtained to be statistically significant at exposure times. The presence and concentration of zeolite significantly reduced the accumulation of lead content in T. tubifex.